Protein Kinase B Alpha (PKBα) Stimulates the Epithelial Sodium Channel (ENaC) Heterologously Expressed in Xenopus laevis Oocytes by Two Distinct Mechanisms - Diyakov, Alexey; Nesterov, Viatcheslav; Mokrushina, Marianna; Rauh, Robert; Korbmacher, Christoph (Cellular Physiology and Biochemistry, 2010)
Kinases contribute to the regulation of the epithelial sodium channel (ENaC) in a complex manner. For example, SGK1 (serum- and glucocorticoid-inducible kinase type 1) enhances ENaC surface expression by phosphorylating Nedd4-2, thereby preventing ENaC retrieval and degradation. An additional mechanism of ENaC activation by SGK1 involves an SGK consensus motif ((616)RSRYWS(621)) in the C-terminus of the channel's α-subunit. This consensus motif may also be a target for ENaC regulation by protein kinase B α (PKBα) known to be activated by insulin and growth factors. Therefore, we investigated a possible role of PKBα in the regulation of rat ENaC heterologously expressed in Xenopus laevis oocytes. We found that recombinant PKBα included in the pipette solution increased ENaC currents in outside-out patches by about 4-fold within 15-20 min. Replacing the serine residue S621 of the SGK consensus motif by an alanine (S621A) abolished this stimulatory effect. In co-expression experiments active PKBα but not catalytically inactive PKBα significantly increased ENaC whole-cell currents and surface expression by more than 50 % within 24 hours of co-expression. Interestingly, this stimulatory effect was preserved in oocytes expressing ENaC with the S621A mutation. We conclude that the acute stimulatory effect of PKBα involves a specific kinase consensus motif in the C-terminus of the channel's α-subunit. In contrast, the increase in channel surface expression caused by co-expression of PKBα does not depend on this site in the channel and is probably mediated by an effect on channel trafficking.